2020
DOI: 10.1016/j.xfre.2020.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of aneuploidy rates between conventional in vitro fertilization and intracytoplasmic sperm injection in in vitro fertilization–intracytoplasmic sperm injection split insemination cycles

Abstract: Objective: To evaluate the influence of insemination methods on outcomes of preimplantation genetic testing for aneuploidy (PGT-A) by assessing PGT-A results in embryos that derived from conventional in vitro fertilization (IVF) versus intracytoplasmic sperm injection (ICSI) in sibling oocytes. Design: Retrospective cohort study. Setting: Single academic IVF center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 26 publications
2
15
1
Order By: Relevance
“…Moreover, as per blastocysts obtained, sperm factors did not exert significant effects on the euploidy rate, although using poor-quality sperm for insemination appears to reduce fertilization and blastocyst formation rates ( Mazzilli et al, 2017 ). Furthermore, univariate GEE analysis demonstrated that other patient or cycle variables evaluated in this study, such as BMI, AMH, ovarian stimulation protocols, and artificial insemination methods, were not significantly correlated with embryo ploidy; these findings were similar to previous reports ( Deng et al, 2020 ; Irani et al, 2020 ; Cascales et al, 2021 ; Pipari et al, 2021 ; Stovezky et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, as per blastocysts obtained, sperm factors did not exert significant effects on the euploidy rate, although using poor-quality sperm for insemination appears to reduce fertilization and blastocyst formation rates ( Mazzilli et al, 2017 ). Furthermore, univariate GEE analysis demonstrated that other patient or cycle variables evaluated in this study, such as BMI, AMH, ovarian stimulation protocols, and artificial insemination methods, were not significantly correlated with embryo ploidy; these findings were similar to previous reports ( Deng et al, 2020 ; Irani et al, 2020 ; Cascales et al, 2021 ; Pipari et al, 2021 ; Stovezky et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…There was no significant difference between IVF and ICSI in terms of the fertilization rate, embryo development or the number of euploid embryos. A retrospective study by Deng et al [ 27 ] found that the numbers of IVF–PGT-A and ICSI–PGT-A had similar embryo aneuploidy and mosaic ratios. Conventional IVF fertilization is unlikely to cause serious contamination during PGT-A.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these findings, several observational studies have shown similar results in terms of the number of embryos available for biopsy, aneuploidy, and mosaicism rates, as well as similar percentages of complete and incomplete diagnoses with either IVF-only or ICSI-only and split insemination approaches. This was true either for PGT for aneuploidies or for PGT for monogenic diseases (46)(47)(48)(49). Therefore, the available bulk of evidence does not suggest an advantage for ICSI, and we can only conclude that the generalized use of ICSI in PGT cycles was adopted on the basis of a ''fear'' of contamination rather than on the basis of solid scientific evidence.…”
Section: Intracytoplasmic Sperm Injection For Few (Continued)mentioning
confidence: 96%